IMPACT OF MODEL PHYSICAL EDUCATION CURRICULUM ON DEXTERITY AND SINISTRALITY AMONG 13 YEARS PREADOLOSCENT SCHOOL BOYS - Ajaz Ahmad Dar (RADJA PUBLIKA, 2023)
ABSTRACT The purpose of the study was to find out the effect of model physical education curriculum on dexterity and sinistrality among 13 years preadolescent school boys. For that purpose 40 right handed dominance preadolescent students from Dream Land educational institute high school Kulgam Jammu and Kashmir India were selected as subjects. 13 years preadolescent school boys were selected as subjects. The subjects were divided into two groups (n=20), the experimental group and control group. The model physical education curriculum was implemented on the experimental group. The curriculum contains four parts A (the physical exercises), B (the yogic asana), C( the theoretical part) and part ‘D’ (the recreational part).The experimental group underwent training for 15 weeks, 4 days a week and 45 minutes per class including warming-up and cooling down exercises. The visual reaction speed on left and right hand were selected as dependable variable was and tested before and after experimental period. The collected data was analyzed by using ANCOVA. Level of significance was fixed at 0.05. The result of the study shows that the model physical education on curriculum helps in development of dexterity among preadolescent school boys.